2022
DOI: 10.1097/aln.0000000000004137
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Labor Analgesia with Dural Puncture Epidural versus Standard Epidural Technique in Obese Parturients: A Double-blind Randomized Controlled Study

Abstract: Background The dural puncture epidural technique may improve analgesia quality by confirming midline placement and increasing intrathecal translocation of epidural medications. This would be advantageous in obese parturients with increased risk of block failure. This study hypothesizes that quality of labor analgesia will be improved with dural puncture epidural compared to standard epidural technique in obese parturients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 29 publications
0
51
0
Order By: Relevance
“…In equation (12), A represented the standard manual segmentation result and B meant the segmentation results 3 Computational and Mathematical Methods in Medicine of GVF-Snake or cervical spine MRI-based ISA. Dice obtained by solution was the ratio of the accurate segmentation part.…”
Section: Segmentation Results Of Cervical Spine Magneticmentioning
confidence: 99%
See 1 more Smart Citation
“…In equation (12), A represented the standard manual segmentation result and B meant the segmentation results 3 Computational and Mathematical Methods in Medicine of GVF-Snake or cervical spine MRI-based ISA. Dice obtained by solution was the ratio of the accurate segmentation part.…”
Section: Segmentation Results Of Cervical Spine Magneticmentioning
confidence: 99%
“…Cervical epidural puncture is an effective way to diagnose and treat acute and chronic pain diseases [ 12 ]. Compared with other sites, the tissue layer thickness of cervical epidural puncture site is increased, and the segment is relatively high, so the risk and difficulty of puncture during the actual operation is relatively high [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this study design, Tan et al 2 found no advantage of the dural puncture epidural technique. They acknowledged that use of a very dilute epidural solution might have lessened the effect of transdural drug passage.…”
mentioning
confidence: 81%
“…In the general parturient population, the overall effect seems to be quite modest at best. In the higher-risk population studied by Tan et al , 2 there were no significant advantages. It may still be possible to identify patients who could benefit (for example, those in whom equivocal loss of resistance is encountered).…”
mentioning
confidence: 88%
See 1 more Smart Citation